Ecosystem services costs of metal mining and pressures on biomes. Issue 1 (January 2020) - Tost, Michael; Murguia, Diego; Hitch, Michael; Lutter, Stephan; Luckeneder, Sebastian; Feiel, Susanne; Moser, Peter
Highlights: The article looks at metal mining's land use and monetizes its impact on ecosystem services. The overall ecosystem services cost is estimated at about USD 5.4 billion/year. Ecosystem services valuation could be a useful policy support tool in all stages of mining where land use aspects play a role. Abstract: Metal mining has significant impacts on the land it uses. With increasing demand for metals, these impacts will continue to intensify. One way to look at land use and related environmental impacts is the concept of ecosystem services (ES), defined as the benefits people derive from services provided by ecosystems. This paper estimates the costs of the reduction of ES due to metal mining`s global land use by analysing four key metal ores – bauxite (aluminium), copper, gold and iron, and by doing so, provides also novel information from which biomes those metals are extracted. The overall ES cost caused by metal mining is estimated at about USD 5.4 billion/year (2016), with about two thirds in forested areas. If added to prices, it would lead to increases of between 0.8 % and 7.9 % for the four commodities studied. The authors do not understand ES valuation as a market-based, stand-alone tool to lower the land impact of metal mining. Other policy tools would have to play a leading role, such as zoning regulations, environmental minimum standards or closure legislation. However, it would be a useful support for such policy tools in all stages of mining where land use aspects play a role.